Recent Learning Innovations: Increasing The Use Of Blogs As Learning Media For Educators - Siswanto, Edhi; Soeharno, Ageng (Universitas Muhammadiyah Jember, 2024)
Educators must be able to apply the latest learning innovations while still utilizing the internet as a learning resource. Today, many blogs and websites are available for teachers and students that allow them to create and learn without limits. However, many educators do not use blogs as a learning medium. The causes include the use of English terminology in some blogs which may be difficult for some students and teachers to understand, lack of knowledge in using blogs as a learning medium, and educators assuming that blogging requires knowledge of computer programming. The core stages of implementing community service activities are socialization, simulation, training and evaluation. Implementation of service activities in the form of training will be held on Saturday 10 February 2024 at SDN Sempusari 1. This training activity starts from 09.00 WIB until 15.00 WIB. The number of participants who took part in the training activities was 17 teachers. The training participants are teachers at SDN Sempusari 1. The results of this training activity are that participants will gain knowledge about how to use free blogging facilities on the Internet. Participants gain knowledge about how blogging features can be used to support learning